AGILE LEADERSHIP AT START-UP CARA BICARA - Oktavia Erlina Dwi , Anggraini; Rita, Mutiarni (STIE PGRI Dewantara Jombang, 2023)
An agile leadership style is an approach that is responsive to business change, with transparency, collaboration, and adaptability. This leadership style suits current business conditions and is open to active and dynamic participation from all organization members. This research is intended to look at the application of Agile leadership in the â€œCara Bicaraâ€ strategy. This research used a qualitative approach to obtain complete information about Agile leadership by leaders at the start-up